The value of Anti-Müllerian hormone in low and extremely low ovarian reserve in relation to live birth after in vitro fertilization. (May 2016) - Reijnders, Igna F.; Nelen, Willianne L.D.M.; IntHout, Joanna; van Herwaarden, Antonius E.; Braat, Didi D.M.; Fleischer, Kathrin
Abstract: Objective: To determine the relation of Anti-Müllerian hormone (AMH) with live birth after in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) in women with (extremely) low ovarian reserve. Study design: This study was a retrospective cohort study in a Dutch tertiary fertility clinic. Between January 2009 and March 2012, AMH levels were measured in infertile women when ≥36 years of age or when showing clinical signs of diminished ovarian reserve, before they underwent IVF or ICSI treatment. Ultimately, 156 women with (extremely) low ovarian reserve were included and evaluated for cumulative live birth rates. Of each woman, only one treatment cycle was analyzed, either the one in which she became pregnant or her first treatment cycle if she did not reach pregnancy. The relation between AMH and live birth was evaluated with multivariable logistic regression analysis. A ROC curve was composed to evaluate the discriminative value of AMH in relation to live birth after IVF/ICSI. Results: Thirty-three out of 156 women (21.2%) gave live birth. Live birth was significantly lower in women with AMH ≤0.1 ng/ml (4/37 women; 10.8%) or AMH >0.1–0.4 ng/ml (7/42 women; 16.7%), compared to women with AMH >0.4–1.05 ng/ml (22/77 women; 28.6%), p < 0.001. Multivariable logistic regression revealed an association between the severity of low ovarian reserve and live birth (per 0.1 ng/ml increase in AMH value, Odds ratio 1.21; 95% CI 1.07–1.36). Conclusions: The level of AMH is related to live birth after IVF/ICSI in women with (extremely) low ovarian reserve. The live birth rate in women with AMH >0.4 ng/ml was significantly higher than in women with AMH ≤0.4 ng/ml. AMH could serve as a tool in the pre-treatment counseling for pregnancy and live birth chances in women with (extremely) low ovarian reserve.